Lateral ankle instability in high-demand athletes: reconstruction with fibular periosteal flap - Benazzo, Francesco (Springer Berlin Heidelberg, 2013)
PURPOSE: Fibular periosteal flaps have been used to address chronic lateral ankle instability, but there are no studies in the literature reporting functional outcomes after this particular procedure in high-demand athletes. We postulated that for chronic instability, nonanatomical reconstruction of the lateral ankle ligament with a fibular periosteal flap will return high-demand athletes to their previous levels of activity. METHODS: Forty patients who had grade III ankle sprain and experienced no success after a course of supervised conservative management lasting at least six months and who had a preinjury Tegner score of ≥6 underwent a lateral compartment reconstruction with a fibular periosteal flap. Each patient was given the Tegner and Karlsson questionnaire and was evaluated by the Zwipp method, Foot and Ankle Outcome Score (FAOS) and the American Orthopaedic Foot and Ankle Society (AOFAS) score at the six-month, one, two and three-year time points. Range of motion (ROM) of the affected ankle was assessed, and stress X-rays were performed. Mean patient age was 24.5 (range17–30) years, and no patient was lost to follow-up. RESULTS: Mean follow-up was 36 (minimum 18) months, mean Tegner scores at the one, two and three-year time points were 8.8, 8.9 and 8.9, respectively, and mean Karlsson scores were 93 ± 5.2, 95 ± 3.1 and 94.9, respectively. AOFAS and FAOS scores improved from a mean of 69.4 and 71.4, respectively, in the preoperative group to a mean of 97.2 and 94.4, respectively, at the last follow-up. The ROM was equal to the contralateral ankle in all but two patients at the two-year follow-up. No major complications were found. CONCLUSION: Nonanatomical ligament reconstruction with a fibular periosteal flap for chronic lateral ankle instability was effective in returning high-demand athletes to their preinjury functional levels.